Corruption distance and equity strategies in cross-border M&As: The moderating roles of political connections - Xiaoyuan Li (PLoS ONE, 2025)
This study explores the impact of corruption distance between home and the host countries on equity strategies in cross-border mergers and acquisitions (M&As). In addition, this study evaluates the moderating roles of two distinctive types of political connections. Analyzing cross-border M&A transactions by Chinese acquirers from 2016 to 2021, this study finds that greater corruption distance significantly increases the equity percentage of acquisitions by Chinese acquirers. This is because a greater corruption distance prompts Chinese acquirers to prefer a higher equity percentage, aimed at mitigating transaction costs and securing control over the target firm. Notably, this study argues that inherent political connections weaken the positive effect of corruption distance on the equity percentage of acquisitions; whereas acquired political connections strengthen its positive effect. In conclusion, this study extends the existing literature of the cross-border equity strategies of enterprises from emerging markets and offers practical insights for Chinese enterprises in managing complex cross-border M&A activities.